Development of facial sexual dimorphism in children aged between 12 and 15 years: a three-dimensional longitudinal study - Koudelová, J; Brůžek, J; Cagáňová, V; Krajíček, Václav; Velemínská, J (Orthodontics & craniofacial research, 2015)
OBJECTIVES: To evaluate sexual dimorphism of facial form and shape and to describe differences between the average female and male face from 12 to 15 years. SETTING AND SAMPLE POPULATION: Overall 120 facial scans from healthy Caucasian children (17 boys, 13 girls) were longitudinally evaluated over a 4-year period between the ages of 12 and 15 years. MATERIALS AND METHODS: Facial surface scans were obtained using a three-dimensional optical scanner Vectra-3D. Variation in facial shape and form was evaluated using geometric morphometric and statistical methods (DCA, PCA and permutation test). Average faces were superimposed, and the changes were evaluated using colour-coded maps. RESULTS: There were no significant sex differences (p > 0.05) in shape in any age category and no differences in form in the 12- and 13-year-olds, as the female faces were within the area of male variability. From the age of 14, a slight separation occurred, which was statistically confirmed. The differences were mainly associated with size. Generally boys had more prominent eyebrow ridges, more deeply set eyes, a flatter cheek area, and a more prominent nose and chin area. CONCLUSION: The development of facial sexual dimorphism during pubertal growth is connected with ontogenetic allometry.
Keywords: Nose; Eyebrows; Face; Lip; Female; brada; Anatomic Variation; dítě; puberta; zobrazování trojrozměrné; Age Factors; optické zobrazování; Imaging, Three-Dimensional; ženské pohlaví; longitudinální studie; Adolescent; tvář; Forehead; věkové faktory; anatomická variace; lidé; Chin; Optical Imaging; Mouth; Sex Characteristics; obličej; Cheek; Photogrammetry; oči; Male; fotogrammetrie; obočí; Eye; ústa; pohlavní dimorfismus; Principal Component Analysis; Child; čelo; nos; analýza hlavních komponent; mužské pohlaví; ret; Puberty; mladiství; Longitudinal Studies; Humans